Plexin-B semaphorin receptors interact directly with active Rac and regulate the actin cytoskeleton by activating Rho. - Driessens, M.H.; Hu, H.; Nobes, C.D.; Self, A.; Jordens, I.; Goodman, C.S.; Hall, A. (Current Biology, 2001)
Semaphorins and their receptors, plexins, are widely expressed in embryonic and adult tissues. In general, their functions are poorly characterized, but in neurons they provide essential attractive and repulsive cues that are necessary for axon guidance [1-3]. The Rho family GTPases Rho, Rac, and Cdc42 control signal transduction pathways that link plasma membrane receptors to the actin cytoskeleton and thus regulate many actin-driven processes, including cell migration and axon guidance [4-7]. Using yeast two-hybrid screening and in vitro interaction assays, we show that Rac in its active, GTP bound state interacts directly with the cytoplasmic domain of mammalian and Drosophila B plexins. Plexin-B1 clustering in fibroblasts does not cause the formation of lamellipodia, which suggests that Rac is not activated. Instead, it results in the assembly of actin:myosin filaments and cell contraction, which indicates Rho activation. Surprisingly, these cytoskeletal changes are both Rac and Rho dependent. Clustering of a mutant plexin, lacking the Rac binding region, induced similar cytoskeletal changes, and this finding indicates that the physical interaction of plexin-B1 with Rac is not required for Rho activation. Our findings that plexin-B signaling to the cytoskeleton is both Rac and Rho dependent form a starting point for unraveling the mechanism by which semaphorins and plexins control axon guidance and cell migration.